117k views
0 votes
Complete the steps to solve this linear equation: 2x + 9(x – 1) = 8(2x + 2) – 5 1.Apply the distributive property: 2x + 9x– 9 = 16x + 16 – 5 2.Combine like terms on each side: 11x – 9 = 16x + 11 3.Use the subtraction property of equality to isolate the variable term: –9 = 5x + 11 Use the subtraction property of equality to isolate the constant: –20 = 5x 4. Use the division property of equality to solve: = x

User Kampu
by
5.3k points

1 Answer

1 vote

Answer: -4

Explanation:

User Adeel Iftikhar
by
5.1k points